Tetranucleotide microsatellites for the barnacle Megabalanus coccopoma (Darwin, 1854). (October 2015) - Reigel, A.M.; Harrison, J.S.; Gleason, D.F.
Abstract: The barnacle Megabalanus coccopoma is indigenous to the tropical Pacific Ocean, but was recently introduced to the coastal waters of the southeastern U.S.A. As part of a larger effort to investigate the population dynamics of this introduction, we designed 13 microsatellite primers specific to M . coccopoma and developed the accompanying polymerase chain reaction (PCR) conditions. We tested these primers on 42 individuals of M . coccopoma collected from two sampling locations in coastal Georgia, USA. The 13 loci developed showed means of 24.5 alleles per locus, 0.93 expected heterozygosity, 0.67 observed heterozygosity, and 0.91 polymorphic information content. The high variation observed within these microsatellite loci makes them useful tools for testing hypotheses related to population genetics, including source-sink dynamics for range expansions and rates of self-fertilization and outcrossing. Highlights: We developed thirteen microsatellite primer pairs for the introduced barnacle, Megabalanus coccopoma . Primer pairs were tested on 42 individuals from two coastal populations in the southeastern U.S. The loci showed means of 24.2 alleles per locus and 0.67 observed heterozygosity. High diversities for each locus make them valuable tools for population genetic studies on M . coccopoma .